A review of structural failures in Ireland - DUCKENFIELD, IAN JAMES (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2018)
Many technical papers have been written and presented to the structural engineering community in Ireland giving details of major projects successfully completed. These projects are on time and under budget. Far more interesting to practising engineers are the cases where things go wrong, and in some cases very badly wrong. Unfortunately the lessons learnt in such cases are hidden from view. No engineer wants to admit that he made an error which now, with the benefit of hindsight, is obvious. The risks of structural failures are extremely low, especially when compared to activities such as car driving and smoking. Nevertheless lives have been lost and life-altering injuries sustained by structural collapses in Ireland. The author has over 40 years of structural design experience and has been collecting examples of failures and near misses. This includes cases where the author acted as an expert witness relating to failures. As part of the research work for the thesis, a number of senior structural engineers have been interviewed and their own experiences of failures collected. The methodology of the collection of the data is given in the thesis noting in particular the sensitive nature of the subject material. This thesis presents 32 of these cases. They involve all the major structural materials and the consequences range from incidents involving multiple fatalities to purely financial loss. The 32 were selected from a longer list on the basis of the extent of the technical details and the interesting lessons learnt. This thesis analyses these cases and outlines the structural issues involved. Further analysis of these cases involves splitting the results into the material used, the cause of the designer?s error or the cause of the contractor?s error. A further breakdown of the results considered the severity of the error. These analyses were undertaken to study if there were any trends. The conclusions of the study are that there are a very wide range of errors made by both the designer and contractor. No cases were found where a new type of failure has taken place ? all the causes are explicable by contemporary structural theory. Although there is no dominant striking pattern to be seen in the cases studied, certain trends can be seen. They are: ? Contractor error is more likely to be the cause of the failure than a structural designer error. The split is around 60% contractor to 40% designer. This is seen as a significant result and should be viewed as significant to those assuming the Assigned Certifier role under the Building Control Amendment Regulations. ? The three potentially most serious failures were all designer errors. The potential outcomes of these errors were multiple fatalities. The three structures were a large bridge which is curved on plan, a set of precast stairs in a school and a building built on concrete piles in ground with heavy chemical contamination. The three cases have significantly different underlying causes. ? All three failures relating to composite decks were contractor errors. Again, the underlying causes are significantly different. This is a small sample but perhaps more careful site supervision of composite decks should take place. ? It is well known that masonry is constructed all over Ireland with little or no structural engineering input. Cases involving multiple fatal incidents with horizontal forces acting on walls are outlined. Contractor error is largely blamed in these. Site supervisors should be aware of the weakness of masonry walls subjected to horizontal pressures from such sources as wind, or crowd loads.
APPROVED
Keywords: Structural Engineering Failures Ireland